2013
DOI: 10.5194/tc-7-1139-2013
|View full text |Cite
|
Sign up to set email alerts
|

Snow spectral albedo at Summit, Greenland: measurements and numerical simulations based on physical and chemical properties of the snowpack

Abstract: Abstract. The broadband albedo of surface snow is determined both by the near-surface profile of the physical and chemical properties of the snowpack and by the spectral and angular characteristics of the incident solar radiation. Simultaneous measurements of the physical and chemical properties of snow were carried out at Summit Camp, Greenland (72 • 36 N, 38 • 25 W, 3210 m a.s.l.) in May and June 2011, along with spectral albedo measurements. One of the main objectives of the field campaign was to test our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
118
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(132 citation statements)
references
References 67 publications
12
118
0
Order By: Relevance
“…Overall, spherical particles caused smaller α b, λ biases than droxtal particles in the clear-sky cases, because of the smaller positive bias in the 1.0-1.4 µm region. The biases in the sphere-based α b, λ and in the associated Swn λ are in qualitative agreement with the biases obtained by Carmagnola et al (2013) using the same modelling approach, although Carmagnola et al (2013) showed the albedo and the absorbed energy integrated over different wavebands and therefore a direct quantitative comparison is not possible.…”
Section: Surface Broadband Albedo and Net Shortwave Radiationsupporting
confidence: 74%
See 1 more Smart Citation
“…Overall, spherical particles caused smaller α b, λ biases than droxtal particles in the clear-sky cases, because of the smaller positive bias in the 1.0-1.4 µm region. The biases in the sphere-based α b, λ and in the associated Swn λ are in qualitative agreement with the biases obtained by Carmagnola et al (2013) using the same modelling approach, although Carmagnola et al (2013) showed the albedo and the absorbed energy integrated over different wavebands and therefore a direct quantitative comparison is not possible.…”
Section: Surface Broadband Albedo and Net Shortwave Radiationsupporting
confidence: 74%
“…Data sets including contemporary in situ observations of albedo and grain texture are few, compared to the large variety of existing snow conditions (Aoki et al, 2000;Carmagnola et al, 2013;Dominé et al, 2006;Nakamura et al, 2001;Painter and Dozier, 2004). These data sets only include short measurement periods, as both spectral albedo and snow observations rely on very laborious and time consuming methods.…”
Section: Introductionmentioning
confidence: 99%
“…10. The differences between the fit and the observation are small; we can note a slight overestimation at 800 nm and underestimation at 970 nm, both of which are very likely due to a small error in the refractive index of the ice already pointed out in other studies (e.g., Carmagnola et al, 2013). In contrast, the overestimation at 1030 nm is more likely an error in the observations resulting from the low sensitivity of the spectrometer in this wavelength range.…”
Section: Illustration Of the Processing Stepssupporting
confidence: 47%
“…They attributed this to the deposition of snow particles having been shrunk by sublimation during blowing snow events. Carmagnola et al (2013) at Summit in Greenland use spectral data in the visible, near-and shortwave infrared and found that tuning the surface layer SSA helped to improve the agreement with the observations but did not explore values as high as Grenfell et al (1994) did. In contrast, Gallet et al (2011) measured SSA vertical profiles at Dome C and obtained radiative transfer calculations in agreement with Hudson et al (2006) observations without adding such a layer.…”
Section: Vertical Representativeness Of Retrieved Ssa Valuesmentioning
confidence: 99%
See 1 more Smart Citation